Indene Derived Phosphorus‐Thioether Ligands for the Ir‐Catalyzed Asymmetric Hydrogenation of Olefins with Diverse Substitution Patterns and Different Functional Groups. Issue 19 (30th March 2021) - Margalef, Jèssica; Biosca, Maria; de la Cruz‐Sánchez, Pol; Caldentey, Xisco; Rodríguez‐Escrich, Carles; Pàmies, Oscar; Pericàs, Miquel A.; Diéguez, Montserrat
Abstract: A family of phosphite/phosphinite‐thioether ligands have been tested in the Ir‐catalyzed asymmetric hydrogenation of a range of olefins (50 substrates in total). The presented ligands are synthesized in three steps from cheap indene and they are air‐stable solids. Their modular architecture has been crucial to maximize the catalytic performance for each type of substrate. Improving most Ir‐catalysts reported so far, this ligand family presents a broader substrate scope, covering different substitution patterns with different functional groups, ranging from unfunctionalized olefins, through olefins with poorly coordinative groups, to olefins with coordinative functional groups. α, β‐Unsaturated acyclic and cyclic esters, ketones and amides were hydrogenated in enantioselectivities ranging from 83 to 99% ee. Enantioselectivities ranging from 91 to 98% ee were also achieved for challenging substrates such as unfunctionalized 1, 1′‐disubstituted olefins, functionalized tri‐ and 1, 1′‐disubstituted vinyl phosphonates, and β‐cyclic enamides. The catalytic performance of the Ir‐ligand assemblies was maintained when the environmentally benign 1, 2‐propylene carbonate was used as solvent. Abstract :